UNDERSTANDING THE CONCEPT OF ELECTRIC CIRCUITS (STATIC, DYNAMIC AND SERIES AND PARALLEL CIRCUITS) - Dinda Amaliana; Dwi Intan Nabila (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Electricity is essential to our lives, as we would struggle to perform everyday tasks without it. Electricity not only provides us with light, but almost all of our technology requires electricity to function. The purpose of this study was to examine how people understand series and parallel circuits by conducting simple experiments in science education. In this study, we used a descriptive qualitative method by examining series and parallel circuits through simple hands-on activities. This research was conducted at STKIP Al Maksum Langkat. The results showed that static electricity occurs when an electric charge remains stationary. Dynamic electricity occurs when an electric charge moves through a wire. In a series circuit, electricity flows through a single path, so if one part is removed, the entire circuit will be broken.